1983
DOI: 10.1002/aic.690290219
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer to gas‐solids suspensions flowing cocurrently downward in a circular tube

Abstract: 13-mm inside diameter tube with uniform heat-flux boundary conditions was investigated using 329-pm spherical glass beads in air. The gas Reynolds number varied from 0 to 30,000 with solids-loading ratios of up to 20 at a gas Reynolds number of 10,000. The suspension Nusselt number, defined in terms of the wallto-gas mixed-mean temperature difference, decreased with increasing solidsloading ratio at high Reynolds numbers, while it changed little from the value for gas alone at low Reynolds numbers. A possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The Reynolds number is also a key parameter in understanding turbulence suppression [1,2,[4][5][6][7][8][9][10][11][12][14][15][16][17][18]. Tien [18] conducted experiments similar in nature to Farbar and Morley [2] and Depew and L. Farbar [5], agreeing with Depew and Farbar's claim that the relationship between the Nusselt number and the solids loading ratio is linear at low Reynolds numbers.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The Reynolds number is also a key parameter in understanding turbulence suppression [1,2,[4][5][6][7][8][9][10][11][12][14][15][16][17][18]. Tien [18] conducted experiments similar in nature to Farbar and Morley [2] and Depew and L. Farbar [5], agreeing with Depew and Farbar's claim that the relationship between the Nusselt number and the solids loading ratio is linear at low Reynolds numbers.…”
Section: Introductionmentioning
confidence: 71%
“…At higher Reynolds numbers, the effect of particles on the suspension heat transfer coefficient is minimal. In contrast, Kim and Seader [17] found that with increasing solids loading, lower Reynolds number suspension flows resulted in little change in the Nusselt number but at higher Reynolds numbers, the increase in solids loading caused a decrease in the Nusselt number. In general, Kim and Seader concluded that increases in heat transfer to the flow could be attributed to the particles breaching the thermal boundary layer reducing its thickness.…”
Section: Introductionmentioning
confidence: 90%
“…Correlations for flowing gas-solid suspensions developed with solid particles other than FCC catalyst or silica-alumina catalysts are available in the technical literature. [7][8][9][10][11] Experimental heat-transfer coefficients using 269-109 µm glass beads were also reported using Sadek's correlation 12 by Lunardelli-Furchi et al 13 There are as well a number of theoretical models to represent the heat-transfer process in gas-solid flowing suspensions. A theoretical approach 14 based on the use of probabilistic multiphase flow equations for vertically flowing gas-solid suspensions was implemented by Bentahar et al 15 An alternative theoretical analysis 16 considers momentum balances, heat balances, and a mixing length parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations for flowing gas−solid suspensions developed with solid particles other than FCC catalyst or silica−alumina catalysts are available in the technical literature. Experimental heat-transfer coefficients using 269−109 μm glass beads were also reported using Sadek's correlation by Lunardelli-Furchi et al…”
Section: Introductionmentioning
confidence: 99%
“…Obvious suspension flow configurations of interest are vertical upflow, vertical downflow, and horizontal and inclined arrangements. The major effort of past research has been on the vertical upflow and horizontal and inclined arrangements, with only the investigations of Kim and Seader , and Brewster and Seader , dealing with heat transfer and pressure drop for gas−solids suspensions in cocurrent vertical downflow. Kim and Seader measured pressure-drop and heat-transfer rates for suspensions of 329-μm glass spheres in air in vertical downflow.…”
Section: Introductionmentioning
confidence: 99%